Upaya Orang Tua Membina Pendidikan Agama Islam Anak di Dusun Embun Pagi Jorong Padang Galanggang - Ramadhan, Pardi; Tamrin, M. Isnando; Alimir, Alimir; Supriadi, Supriadi (Sekolah Tinggi Agam Islam Sumatera Medan, 2021)
This study aims to analyze the efforts of parents to foster their children's Islamic religious education. The focus of the study is on three things, namely the form of effort, supporting factors, and obstacles. This study analyzes the efforts made by parents in Embun Pagi Hamlet, Jorong, Padang Galanggang. The research method used is a descriptive study-based qualitative. Data collection techniques used are observation, interviews, and documentation studies. The data obtained were then analyzed using the Miles and Huberman technique, namely data reduction, data display, and conclusions. The results of the study explain that the form of efforts taken are involving children in non-formal religious education, fostering children's religious practices at home, involving children in religious traditions based on local wisdom, familiarizing children to grow up in the surau. The supporting factors for the implementation and success of these efforts are the high motivation and expectations of parents for their children, coupled with a religious village environment. However, there are also inhibiting factors, namely the busyness of parents at work which is an obstacle to not being able to fully control the religious development of children.